Workforce Strategic Importance: Boosting Organizational Performance - Ananta, Jessica Verga; Nugroho, Sidiq Permono (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study investigates the influence of Workforce Strategic Importance and HR Flexibility on Strategic Human Capabilities and their subsequent impact on Organizational Performance within higher education institutions, focusing on the Faculty of Economics and Business, Universitas Muhammadiyah Surakarta (FEB UMS). The research highlights how human capital adaptability and strategic alignment serve as critical determinants of organizational success.Methodology: A quantitative research design was employed by distributing structured questionnaires to 72 permanent lecturers, assessed using a five-point Likert scale. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0 to evaluate construct validity, reliability, and structural path relationships among variables. The conceptual model integrates four main constructs: Workforce Strategic Importance, HR Flexibility, Strategic Human Capabilities, and Organizational Performance.Results: The results reveal that both Workforce Strategic Importance and HR Flexibility have positive but insignificant direct effects on Organizational Performance. Conversely, both variables significantly enhance Strategic Human Capabilities, which in turn demonstrate a strong positive influence on Organizational Performance. These findings confirm that Strategic Human Capabilities act as an essential mediating mechanism in translating HR initiatives into performance outcomes.Applications/Originality/Value: This study reinforces the Resource-Based View (RBV) by empirically demonstrating that capability development is the core mechanism through which HR strategies contribute to competitive performance in higher education. The findings provide actionable insights for institutional leaders in designing strategic HR practices that strengthen lecturer capability, adaptability, and contribution. Future studies are encouraged to expand sample sizes, incorporate comparative settings, and examine additional HR determinants such as Technical HRM, leadership style, and employee motivation to further enrich performance improvement strategies.